TINJAUAN WAKTU PENYEDIAAN BERKAS REKAM MEDIS PASIEN LAMA RAWAT JALAN GUNA MENUNJANG MUTU PELAYANAN DI RUMAH SAKIT TNI AU DR. M. SALAMUN BANDUNG - Suharto ,; Encep Hada (Jurnal TEDC, 2021)
Based on the results of a preliminary study on January 13, 2020 to January 17, 2020, and based on information from several outpatient installation officers, the implementation of providing medical record files for long outpatients to the polyclinic is still not optimal. Researchers obtained results from interviews with the distribution section, found that outpatient medical record files were late to the polyclinic causing nurses to immediately take them to the distribution section. From the average number of patients per day as many as 520 patients who registered, it was found that 137 outpatient medical record files were late to the polyclinic. The purpose of this study was to determine the time of providing medical record files for long outpatient services at RSAU Salamun Bandung. The research method used is descriptive research method and data collection techniques by observation, interviews, and literature study. The results showed that the provision of medical record files was still not good. The number of fast medical record files is 5965 or 78% and the number of medical record files is 1692 or 22% later, so it can be seen that on average one old patient in the time of providing medical record files for long outpatients carried out in outpatient services at RSAU Salamun Bandung is 19 minutes, so the results obtained in the field are considered long because they exceed the target of the standard that should be 10 minutes. It is recommended for RSAU Salamun Bandung that the outpatient registration service and services at the polyclinic take place at the same time, and it is better for the storage officer and distribution officer to inform the polyclinic when the file is not found.